Adenosine Depletion as A New Strategy to Decrease Glioblastoma Stem-Like Cells Aggressiveness - Ignacio Niechi; Atenea Uribe-Ojeda; José Ignacio Erices; Ángelo Torres; Daniel Uribe; José Dellis Rocha; Pamela Silva; Hans G. Richter; Rody San Martín; Claudia Quezada (Cells, 2019)
Glioblastoma is the brain tumor with the worst prognosis. This is mainly due to a cell subpopulation with an extremely aggressive potential, called glioblastoma stem-like cells (GSCs). These cells produce high levels of extracellular adenosine, which are increased even more under hypoxic conditions. Under hypoxia, adenosine signaling is related to HIF-2α expression, enhancing cell aggressiveness. Adenosine can be degraded using recombinant adenosine deaminase (ADA) to revert its pathological effects. The aim of this study was to degrade adenosine using ADA in order to decrease malignancy of GSCs. Adenosine depletion was performed using recombinant ADA. Migration and invasion were measured by transwell and matrigel-coated transwell assay, respectively. HIF-2α-dependent cell migration/invasion decreased in GSCs treated with ADA under hypoxia. MRPs-mediated chemoresistance and colony formation decreased in treatment with ADA. In conclusion, adenosine depletion using adenosine deaminase decreases GSCs aggressiveness.